2020
DOI: 10.3389/fpsyt.2020.00651
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Attitudes Toward and Experience of Non-Suicidal Self-Injury in Adolescents: A Qualitative Study

Abstract: Background Non-suicidal self-injury (NSSI) is prevalent in adolescents and brings a series of serious consequences to their well-being. However, little is known about parents’ attitude toward NSSI in Chinese adolescents. The study aims to investigate the parents’ attitudes toward and perceptions of adolescents who have engaged in NSSI behaviors, and the impact of NSSI on their parents. Methods Purposive sampling was used in the study. The biological parents of adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…However, participants did not receive sufficient attention and appropriate support from their parents, teachers and friends. 26 Similar to a previous study in the UK, our participants felt patronised and ignored. 27 Some parents of our adolescents considered self-injury to be a shameful behaviour, and these adolescents felt humiliated by their parents.…”
Section: Discussionsupporting
confidence: 75%
“…However, participants did not receive sufficient attention and appropriate support from their parents, teachers and friends. 26 Similar to a previous study in the UK, our participants felt patronised and ignored. 27 Some parents of our adolescents considered self-injury to be a shameful behaviour, and these adolescents felt humiliated by their parents.…”
Section: Discussionsupporting
confidence: 75%
“…Self-injurious behavior among young people applies as an important risk factor for the prediction of a borderline personality disorder ( 14 ). Unfortunately, many parents have no knowledge of NSSI and its treatment and thus suffer from great emotional stress because of it ( 15 ). An additional risk factor is the strong association between NSSI and suicidal behavior ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most parents lack related knowledge and awareness of mental health. Previous research found that when parents know their children engaged in self-harm, their first reaction is to ignore [ 29 ]. Thus, until their children have serious SRBs, professional institutions were the last resort for parents.…”
Section: Discussionmentioning
confidence: 99%